👤

cine ma poate ajuta ??​

Cine Ma Poate Ajuta class=

Răspuns :

Răspuns:

a)

[tex]\sqrt{2} * (\frac{4}{\sqrt{18}} +\sqrt{0,(2})+\sqrt{3}*(\sqrt{0,(3)}+\frac{2}{\sqrt{3}})\\\frac{\sqrt{2}*4}{3\sqrt{2}}+\sqrt{2}\sqrt{\frac{2}{9}}+\sqrt{3}\sqrt{\frac{3}{9}}+\frac{\sqrt{3}*2}{\sqrt{3}}=\\\frac{4}{3}+\frac{2}{3}+\frac{3}{3}+2=\frac{6}{3}+1+2=2+1+2=5[/tex]

b)

[tex]\sqrt{5}*(\frac{5}{3*\sqrt{5}}+\sqrt{0.(5)}+\frac{\sqrt{20}}{6})-\sqrt{6}*(\sqrt{0.(6)}+\frac{2\sqrt{2}}{\sqrt{3}})=\\\frac{\sqrt{5}*5}{3*\sqrt{5}}+\sqrt{5}*\sqrt{\frac{5}{9}}+\frac{2\sqrt{5}*\sqrt{5}}{6}-\sqrt{6}*\sqrt{\frac{6}{9}}+\frac{2*\sqrt{2}*\sqrt{6}}{\sqrt{3}}=\\\frac{5}{3}+\frac{5}{3}+\frac{5}{3}-\frac{6}{3}+4=\frac{15}{3}-2+4=5-2+4=7[/tex]

Explicație pas cu pas: